Teaching translation and interpreting courses to students’ lacks and wants: An exploratory case study of prioritizing instructional objectives - Li 李向东 Xiangdong (Círculo de Lingüística Aplicada a la Comunicación, 2019)
Though formulation and prioritization of instructional objectives is an important link in the chain of course design, little research has been done in this regard in the field of translation and interpreting (T&I) education. This paper aims at demonstrating how to prioritize instructional objectives in implementing a consecutive interpreting course by inviting students to voice their wants and lacks. Thirty undergraduates and one instructor contributed to data collection through questionnaires and self-evaluation reports. Results of students’ pre-course wants and lacks helped prioritize the objectives formulated in the course design phase. Their pre-course post-course gains and post-course lacks were used to measure teaching effectiveness of prioritized instruction and learning, direct the design of the subsequent course, and thus achieve coordination and integration between courses in the overall T&I curriculum. The current study may inspire colleagues to become selfreflective researchers by formulating and prioritizing their instructional objectives and to contribute to instructional effectiveness at the course level and promote course sequencing and integration at the program level.